O estudo da guerra e a formação da liderança militar brasileira (1996-2004). - Oliveira, Tânia Regina Pires de Godoy Torres de (2004)
This study in the educational field displays the results of the bibliographic, documental and field researches. These were studies about the war through the teaching of Military History as this discipline is taught in the Brazilian Armed Forces schools. It highlights the study of war in History classes, the formation of the war leader in Brazil prepares the soldier for his war performance but this educational orientation has proven insufficient because it does not consider characteristics that are specific to the Brazilian military personnel. That s an educational process that focuses the History of War in a positive way and that does not necessarily prepare the officer for his career in the Brazilian society, a society that is not interested in the topic of Defense. That lack of interest can be explained by the fact that Brazil has rarely run any risks of attack against its territory or its sovereignhood. That s why the people find civical or subsidiary military action to be more important than actions of war. The Army schools programs do not approach polemic topics in the Armed Forces trajectroy in the Brazilian society. That s because our forces have never been on a battlefield. They have mostly done territorial defense and administration. Moreover, it has been involved in both social and political issues. Therefore, its educational formation aims for a performance that will not actually take place in Brazil. It s insufficient for the officer in his actual professional life. To prove our theory, we analyze the politics concerning national defense. These politics have existed since 1996 and we ll also see what they say about military performance and its scarce presence in the teaching-learning process. The element that brings about such analysis is the Military History content because it shows that the civilians society keeps getting more and more estranged from defense issues. Next, we present aspects of Military History in the three Brazilian army schools from 1996 through 2004. We also present its specific features in the teachinglearning process, the orientation for a study of war as an educational element in the preparation of an officer and the way this discipline is regarded by education authorities. We also show the way students of the three Brazilian military schools see Military History, a regular part of their formation, and the way they see their own preparation for the military career. Finally, we reflect upon the political and institutional role of the Brazilian Armed Forces, as it is in the National Defense Policy. We also reflect upon the difficulties to build a program that encloses the multiple functions to be performed by a Brazilian military officer nowadays.